2021
DOI: 10.1111/ijtd.12256
|View full text |Cite
|
Sign up to set email alerts
|

A new path to training transfer: Transformational trainers and psychologically empowered training participants

Abstract: Successful training transfer is necessary for employees to adapt to this fast‐changing working world. In this study, we investigate whether transformational trainer behaviour can inspire training participants to change their self‐concept during training and whether this is related to increased training transfer. Following the self‐concept based theory, we examine the relationship between transformational trainer behaviour and training transfer, mediated by psychological empowerment. Moreover, we test a cross‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…The absence of a relationship between training value and training transfer is obviously because psychological empowerment and motivation to transfer are needed to play mediating roles. The findings on motivation to transfer and its relationship with training transfer and employee engagement as well as psychological empowerment and its relationship with motivation to transfer, employee engagement and training transfer are similar to the findings by Bhatti et al (2013), Na-nan et al (2017, Na-nan and Sanamthong (2020), Jose and Mampilly (2014), Bansal and Thakur (2013), Gong et al (2020), Meng and Sun (2019), Shah et al (2019), Sharma and Garg (2017) and Creon and Schermuly (2020). Similar to the finding of Salamon et al (2022b), the employee engagement and training transfer relationship was not in line with the assertion of Nafukho et al (2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The absence of a relationship between training value and training transfer is obviously because psychological empowerment and motivation to transfer are needed to play mediating roles. The findings on motivation to transfer and its relationship with training transfer and employee engagement as well as psychological empowerment and its relationship with motivation to transfer, employee engagement and training transfer are similar to the findings by Bhatti et al (2013), Na-nan et al (2017, Na-nan and Sanamthong (2020), Jose and Mampilly (2014), Bansal and Thakur (2013), Gong et al (2020), Meng and Sun (2019), Shah et al (2019), Sharma and Garg (2017) and Creon and Schermuly (2020). Similar to the finding of Salamon et al (2022b), the employee engagement and training transfer relationship was not in line with the assertion of Nafukho et al (2017).…”
Section: Discussionsupporting
confidence: 88%
“…The finding of Richter and Kauffeld is supported to some extent as motivation to transfer played a partial mediating role in that study unlike what we found in this paper. Psychological empowerment also plays the same mediating role as motivation to transfer in the relationship between training value and training transfer confirming the assertions of Menon (2001) and Creon and Schermuly (2020). Despite the stance of Salamon et al (2022b) and Nafukho et al (2017), employee engagement did not have a mediating effect in this study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Dixit and Sinha (2022) showed that the effectiveness and efficiency of training transfer tools were strongly correlated and enabled the workplace application of skills and knowledge. Creon and Schermuly (2022) revealed that the training individuals' psychological empowerment mediated the positive relationship between transformational trainer behavior and training transfer. Kalule et al (2019) stated that perceived value of content mediated extension agents' supervision support in predicting farmers' intention to apply what they had learned during extension training programs.…”
Section: Introductionmentioning
confidence: 97%